Response Of Nilaparvata Lugens (Stal.) Hemiptera; Delpacidae To The Application Of Deltamethrin Insecticides At Sublethal Concentrations - Awaluddin Awaluddin; Waode Siti Anima Hisein; Siska Efendi; La Oge; Cecep Ijang Wahyudin (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
The initial population of Nilaparvata lugens was obtained from the field and developed in the entomology and toxicology laboratory of the plant protection department of Halu Oleo University. This study began with mass cultivation of the N. lugens insect pest. This was followed by selecting the LC50 concentration based on mortality at 72 hours after treatment. The results of the probit analysis found an LC50 value 3.16 ml/L for the insecticide deltamethrin. The high recommended concentration found for the insecticide deltamethrin is suspected because it is not recommended for use on N. lugens in rice fields. Increasing the frequency of application at sublethal concentrations (LC10 and LC25) was shown to trigger an increase in the resurgence ratio of 1.50 and 1.70 times, respectively, compared to the control group.